Implementation of Islamic Religious Education Learning in Building Religious Character in Students (Explorative Study SMP N 1 and SMP N 3 Bringin) - Arrosyid’, Muhammad Harun; Nursikin, Mukh (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This study aims to find out how the implementation, impact and supporting and inhibiting factors of Islamic Religious Education learning in building religious character in students of SMP N 1 Bringin and SMP N 3 Bringin. There are main discussions in this study, namely: (1) the implementation of Islamic Religious Education learning in building religious character (2) the impact of the implementation of Islamic Religious Education learning in building religious character (3) supporting and inhibiting factors for the implementation of Islamic Religious Education learning in building religious character. The researcher uses a qualitative approach through interview, observation, and documentation methods. Meanwhile, the data analysis technique uses qualitative data analysis with procedures for collecting, reducing data, presenting data, and drawing conclusions which are then verified. The findings of this study are: 1) The implementation of Islamic Religious Education learning in building religious character in SMP N 1 & 3 Bringin students is carried out through the process of planning, implementation and evaluation; 2) The impact of the implementation of Islamic Religious Education learning at SMP N 1 Bringin includes: (1) Fostering Self-Discipline; (2) Increasing Tolerance Attitudes; (3) Increasing Social Awareness; (4) Increasing Spiritual Awareness; (5) Ethical and Moral Development.